The Role of Social Media in Disseminating Information About The Church in GMIM Baitani Matani: Peran Media Sosial dalam Penyebaran Informasi Gereja di GMIM Baitani Matani - Keyra N. Wakary; Stefanus A.G. Lumintang; Claudya Makalew; Khensi P. Panekenan; Vanny Nancy South; Denny Adry Tarumingi; Maria Elisa Tulangouw; Riedel Ch. Gosal (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This paper discusses how social media works as a communicative and spiritual space in Gereja Masehi Injili di Minahasa (GMIM), a synodal Protestant church in Minahasa. This study examines the application of social media in sharing church information, congregational interactions, and spiritual life. An explanatory sequential mixed-methods design was used, which entailed a survey of 34 congregants, in-depth interviews, and digital ethnography of the official accounts of GMIM. Quantitative data convey the trends of platform usage, time clocked, role, perceived spiritual influence, and involvement in online religious materials, whereas qualitative data demonstrate how leaders and members perceive the chances and threats of digital communication. The results show that social media is integrated into the life of congregations and represents a digital continuation of communal relationships, assisting in the provision of information, worship resources, and support. Meanwhile, the respondents referred to ambivalence, acknowledging social media as a source of grace and a distracter, conflict, and superficial religiosity simultaneously. The research also reveals that the digital communication used by GMIM is, to a great extent, one-sided, although the congregants want to interact more dialogically through two-way communication. The article proposes that the church should have cohesive policies on digital communication, invest in digital literacies, and unite online practices with embodied worship and diaconal action so that social media may be used as a place of proclamation, koinonia, and Christian service and not as a convenient channel to make announcements.